Sata vuotta vesihuoltoa Suomessa 1917-2017 - P. Rajala, Riikka (Tampere University Press, 2017)
100 years of water supply and sanitation in Finland This book is written by Petri S. Juuti, Tapio S.Katko & Riikka P. Rajala. Finland is known as a land of thousands of lakes. Yet, there are regions in Finland where lakes are very few and the lack of fresh water is an ordinary problem. Finland is quite unique in Fennoscandia as to its water resources. The country has some 56 000 lakes with a minimum area of one hectare and all together 200000 lakes. Ground water occurs in alluvial eskers formed during ice ages, the last of which ended some 10 000 years ago. Nowadays some 60 per cent of the people use natural or artificially recharged ground water. However, areas lower than 50-60 metres above sea level have problems with water quality due to geological reasons. In such areas bigger cities use surface water for their water supply or acquire their raw water from sources further away. The book shows us how water supply and sanitation have developed in Finland during years of political independence starting from the year 1917.